1987
DOI: 10.1038/bjc.1987.165
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization by misonidazole in CCNU-treated spheroids and tumours

Abstract: Summary Misonidazole has been demonstrated to enhance the cytotoxicity of several common antineoplastic drugs in vitro and in vivo, and its mechanism of action as a chemosensitizer, though still unknown, is thought to be dependent upon hypoxia. We have used fluorescence-activated cell sorting to evaluate chemopotentiation by misonidazole as a function of cell position in V79 spheroids and KHT tumours. CCNU toxicity was enhanced in all cell subpopulations of both tumours and spheroids, with greater consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…This has been demonstrated by several investigators. Durand and Chaplin (1987) used the fluorochrome Hoechst 33342 to separate tumour cells in fractions as a function of distance from the blood vessels. They found that the chemosensitisation by MISO in KHT tumours treated wth CCNU was almost constant throughout the tumour, irrespective of the oxygenation status of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated by several investigators. Durand and Chaplin (1987) used the fluorochrome Hoechst 33342 to separate tumour cells in fractions as a function of distance from the blood vessels. They found that the chemosensitisation by MISO in KHT tumours treated wth CCNU was almost constant throughout the tumour, irrespective of the oxygenation status of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…An obvious interpretation is that SR2508 (not a known myelotoxic agent) may potentiate the toxicity of cyclophosphamide to bone marrow stem cells. This may occur as a result of GSH depletion in oxic cells as occurred in peripheral mononuclear cells; enhanced toxicity of cyclophosphamide (Grau et al, 1990) and other alkylators (Durand & Chaplin, 1987;Horsmann et al, 1989) to oxic cells is welldescribed in vivo and in spheroids. Allalunis et al have shown in addition that a proportion of normal marrow cells exist in a hypoxic environment (Allalunis et al, 1983).…”
Section: Discussionmentioning
confidence: 99%